Mathematics Teaching Anxiety of Indonesian Elementary School Teachers in Online Learning during COVID-19 Outbreak - Argaswari, Deshinta Puspa Ayu Dwi; Hapsari, Aulia Kirana (FKIP Universitas Lampung, 2022)
This study aims to identify the scale of mathematics teaching anxiety among Elementary teachers during online learning during the Covid-19 Pandemic at Pekayon district and determine the mathematics anxiety in teaching during the pandemic. The research method that used for this research is a mixed method. The study was conducted on 42 mathematics teachers who teach online learning. Data were collected through a 19-item Mathematics Teaching Anxiety Scale (MTAS) questionnaire. The results indicated that six people (14%) were classified as having high anxiety, twenty-eight people (67%) as having moderate anxiety, and eight people (19%) as having low anxiety. The factors that cause anxiety in teaching mathematics in general are the factors of Student-Directed Mathematics Teaching Anxiety. However, Teachers with high anxiety, teachers with low anxiety, and teachers with normal anxiety differ greatly in preparing materials and learning tools and delivering online learning materials. Keywords: mathematics teaching anxiety, MTAS, online learning, Covid-19 pandemic DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp595-605